Pengembangan Modul Pembelajaran Biologi pada Materi Interaksi dalam Ekosistem Berbasis Pendekatan Contextual Teaching And Learning (CTL) Kelas X di SMA Negeri 1 Tilango - Desriyanti Tane; Ramli Utina; Marini Susanti Hamidun; Masra Latjompoh; Frida Maryati Yusuf; Abubakar Sidik Katili (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
This research aims to describe the validity, practicality and capability of student learning outcomes using Contextual Teaching and Learning (CTL) based learning modules . The test subjects in this research involved 20 class X students of SMA Negeri 1 Tilango for the 2023/2024 academic year. The CTL-based module developed refers to the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model which is limited to the limited-scale trial development stage. The research results based on the CTL-based Module show the feasibility value of the valid criteria, the practicality of obtaining a score in the score range of 81%-100%, the learning outcomes of students using the N-Gain formula obtain a percentage value of 0.61% with medium criteria, so that the CTL-based Module is developed suitable for use as a learning medium to improve student learning outcomes on interaction material in ecosystems in class X SMA Negeri 1 Tilango.